Pengaruh Transparansi, Akuntabilitas, dan Pengawasan Terhadap Pengelolaan Dana Desa (Studi Kasus Desa Bangun Harjo Kecamatan Pelepat Ilir Kabupaten Bungo) - Alfala, Miftakul Khoir; Mukhzarudfa, Mukhzarudfa; Mansur, Fitrini (Universitas Batanghari Jambi, 2024)
The aim of this research is to find out how the management of village funds in Bangun Harjo Village, Pelepat Ilir District, Bungo Regency is influenced by accountability, transparency and supervision. The target population for this research was 50 people including village officials, BPD, and community leaders. The sampling strategy used was saturated sampling. Using SPSS version 25 software, quantitative methods and multiple regression analysis were used in this descriptive research. Based on test findings, village financial management in Bangun Harjo Village has improved significantly through accountability, openness and supervision.